Correlation between Meibum Quality and Ocular Surface Staining in Obstructive Meibomian Gland Dysfunction - Ike Hikmawati; M Rinaldi Dahlan; Susi Heryati (Majalah Oftalmologi Indonesia, 2016)
Background: Obstructive Meibomian gland dysfunction (MGD) leads to a decreased availability ofmeibomian lipid at the ocular surface that could result in ocular surface damage due to increasedevaporation of the aqueos layer of the tear film. Alteration of meibomian oil (meibum) is one of thecausative factors of the obstructive process and the sign of the obstruction as well.Methods: This was a cross-sectional study using Spearman’s Rank Correlation Coeeficient (rs) to findcorrelation between meibum quality and the ocular surface damage. Subjects were patients withobstructive MGD selected consecutively in Infection and Immunology Unit of Indonesia National EyeCenter, Cicendo Eye Hospital. There were 48 eyes from 29 subjects comprised 28 inflamed MGD and20 non-inflamed MGD. Meibum quality was assessed by performing digital expression on eightmeibomian glands located on the lower lid. Ocular surface damage was done by performing cornealstaining using fluorescein eye drop and conjunctival staining using Lissamine Green strip. The stainingresults were then documented using camera of slit lamp biomicroscopy and based on the documentation,scoring of the ocular surface staining was done using National Eye Institute/Industry (NEI)scheme/diagram.Results: This study showed no correlation (rs: -0.067) between meibum quality and ocular surfacedamage (p=0.652). Statistical analysis was also done on subjects categorized based on inflammationon the eyelid and there was found correlation (rs: 0.238) between meibum quality and ocular surfacedamage in inflamed MGD (p=0.312).Conclusion: There is no correlation between the quality of meibum and ocular surface staining.Keywords: obstructive MGD, quality of meibum, ocular surface damage